“Forum Shopping” and the European Union Law - A. A. Vinogradov (Московский журнал международного права, 2010)
The article is connected with the choice of jurisdiction in cross-border transactions in the European Union. The key point is the substance of Forum Shopping procedure, its peculiarities and application. Due to the increase in cross-border transactions in the European Union the parties frequently use Forum Shopping procedure to choose an appropriate jurisdiction. Such application results in legal confusion, abuse or unfair competition affecting the internal market. Because of utmost importance of these issues the article focuses on “Forum Shopping” and analyses its theoretical as well as practical role.